2022
DOI: 10.3389/fmed.2022.901937
|View full text |Cite
|
Sign up to set email alerts
|

Hematological indices in the adult saudi population: Reference intervals by gender, age, and region

Abstract: IntroductionHematological parameters are critical in disease diagnosis, management, and monitoring; however, complete blood count (CBC) reference intervals vary across populations. The aim of the current study was to provide the reference ranges of hematological parameters/indices in the healthy adult Saudi population.MethodsA multicenter retrospective cross-sectional study was conducted with a sample of employees who were screened pre-employment from January 2015 to December 2019, at tertiary care hospitals i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 57 publications
0
6
1
Order By: Relevance
“…In comparison with other RIs studies, we obtained higher UL of Hb (18.0 g/dL) in males and PLT in females (443 ×10 6 /μL) compared to other Arab countries (Oman, Iraq, Qatar, Morocco, Sudan) for Hb and PLT [13,40,[51][52][53]. Moreover, S3 Fig shows that our UL of Hb in males and PLT in females are mostly higher than those of four previously published studies on Saudi population (17.9 g/dL, 303×10 9 /μL; [21] 17.2 g/dL, 334×10 9 /μL [54]; 17.5g/dL, 337×10 6 /μL [19]; 18.0g/dL, 367×10 6 /μL [50]) respectively. The reason for the higher-side shift of RVs for hemoglobin and PLT compared in this study could be due to our use of improved statistical approaches including: 1) the parametric method which is robust to extreme values prevalent in skewed distributions unlike nonparametric method [31], and, 2) the LAVE procedure which is effective in reducing the influence of highly prevalent subclinical conditions such as anemia with and without iron deficiency.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…In comparison with other RIs studies, we obtained higher UL of Hb (18.0 g/dL) in males and PLT in females (443 ×10 6 /μL) compared to other Arab countries (Oman, Iraq, Qatar, Morocco, Sudan) for Hb and PLT [13,40,[51][52][53]. Moreover, S3 Fig shows that our UL of Hb in males and PLT in females are mostly higher than those of four previously published studies on Saudi population (17.9 g/dL, 303×10 9 /μL; [21] 17.2 g/dL, 334×10 9 /μL [54]; 17.5g/dL, 337×10 6 /μL [19]; 18.0g/dL, 367×10 6 /μL [50]) respectively. The reason for the higher-side shift of RVs for hemoglobin and PLT compared in this study could be due to our use of improved statistical approaches including: 1) the parametric method which is robust to extreme values prevalent in skewed distributions unlike nonparametric method [31], and, 2) the LAVE procedure which is effective in reducing the influence of highly prevalent subclinical conditions such as anemia with and without iron deficiency.…”
Section: Discussioncontrasting
confidence: 53%
“…This kind of association between platelet and Fe levels may explain the high median platelet level in this study for adult Saudi females compared to other countries but at the same time it is compatible to levels for Kenyan females as shown in Fig 3 . The scientific mechanism behind this association is not clear, but it is suggested that a decrease in iron can induce thrombocytosis by changing the proliferation and differentiation of pluripotent erythroid and megakaryocyte precursors in bone marrow [49]. Although a recent study showed that thrombocytosis in Saudi females is higher than males (6.34% vs. 1.08%) [50], but still no available study investigated the incidence of thrombocytosis in Saudi females in comparison to other countries. Our study shows that the median value of MPV in Saudi females (8.16 fL) is lower than those in Turkey (8.9fL) and Ghana (10.7 fL).…”
Section: Discussionmentioning
confidence: 99%
“…Hemoglobin values, RBC count, and hemoglobin F levels are relatively close to the normal ranges detected in the healthy adult Saudi population. However, MCV and MCH levels are lower than the index values (21). This observation can be related to a high prevalence of latent iron de ciency and alpha thalassemia in the Saudi population.…”
Section: Discussionmentioning
confidence: 80%
“…Sex hormone fluctuations in females were responsible for lower iron and ferritin levels [ 39 ] that were also associated with lower concentrations of MCH, MCHC, PDW, and higher levels of transferrin. Platelets were also involved in these fluctuations, with increased platelets concentrations in females due to hormones or compensation due to menstruation [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%